Sesc Aleixo: projeto de um centro de recreação e serviços para a cidade de Manaus - Barreira, Airton Fonseca (Brasil, 2024)
This final graduation project presents an architectural proposal for the construction of a Social Service of Commerce (Sesc) unit in the Aleixo neighborhood, in Manaus, with the aim of offering an inclusive, accessible and attractive recreational space to the local population. The initiative aims to meet the community’s leisure, cultural and educational needs, especially in a city where recreational infrastructure is limited and public spaces face abandonment and vandalism.